PENGARUH DISIPLIN KERJA DAN SISTEM KOMPENSASI TERHADAP KINERJA PENGAWAI (STUDI PADA BALAI PELAKSANA TEKNIS BINA MARGA WILAYAH SEMARANG) - Stella, Bonaventura; Djastuti, Indi (Diponegoro Journal of Management, 2015)
This study aimed to analalyze the influence of labor discipline and compensation system on employee performance of Badan Pelaksana Teknis Bina Marga Wilayah Semarang. There are 2 independent variables in this study : labor discipline and compensation system on employee performance. This study uses census method with 50 respondents. The analytical method used in this study is multiple linear regression. Based on statistical dataÂ  analysis, indicators in this study are valid and reliable. In the classical assumption test, regression models multicoloniarity trouble-free, does not occur heteroscedasticity, and normal distribution. The result of this study showed that labor dicipline variable has positive and significant effect on employee performance, and compensation system variable hasÂ Â  positive and significant on employee performance. Therefore, this study is expected to bring benefits to the â€œBalai Pelaksana Teknis Bina Marga Wilayah Semarangâ€, the employess, and the government as reference material to determine issues relating to the performance of â€œPegawai Negeri Sipilâ€ until later to do a policy to solveÂ  these problems.